Pushing an existing villa in Dubai to nearly Zero Energy Building passing through AL SA’AFAT rating system - Al Ali, Meera Hamid Obaid (2017)
Our surrounding environment is effected significantly due to the buildings impact which is a result of excessive energy consumption. Residential and commercial buildings use about 40% of the world total primary energy (Pless & Torcellini, 2010). During the years between 1980 and 2003 the consumption of energy had been doubled and it is still increasing and by 2025 it is expected to increase even more by 50% (Pless & Torcellini, 2009). Therefore, many countries already started to take actions regarding that. Taking into consideration one city, during the spectacular evolution of Dubai, many improper activities that have a negative effect on the environment had been spread between almost all sectors. Activities such as transportation, construction and daily routine habits had been attached by practices that have a detrimental impact on the surrounding environment. The excessive irreverence by consumers due to lack of awareness, led the governments and the associations in charge to take actions to prevent the aggravation of this phenomenon. Therefore, various regulations had been set to limit various problems in order to restore the order and aware people about the risks and the consequences of their improper habits. Recently, Dubai Municipality is finalizing a green buildings rating system called ‘AL SA’AFAT’, this rating system is divided into four certificates which are; bronze, silver, gold and platinum. Moreover, a city like Dubai that grows very fast may need better solution than green buildings. Since buildings have a huge impact on the surrounding environment, minimizing this impact as much as possible should act as an option for Dubai. However, many different countries already set their roadmaps to reach their targets for nearly Zero Energy Buildings or Page | ii Net Zero Energy Buildings in order to participate in improving the energy performance and building efficiency of new buildings. Therefore, this research aims to push existing villas in Dubai into nearly Zero Energy Building passing through ‘AL SAFAT’ rating system. The main challenge was to build a computer model for an existing villa taking into consideration the design, construction materials, orientation and exact location using IES-VE software. After analyzing the performance and making sure of matching the current situation of the villa using the software, implementing the requirements of ‘AL SA’AFAT’ rating system level by level comes next. This procedure showed a huge reduction in energy consumption that actually reached 61.1% when comparing the existing situation of the villa with the bronze level which is the lowest level in ‘AL SA’AFAT’ rating system. While the process of transforming the bronze level to silver, gold and platinum showed also reduction in energy consumption as the follow; 63.3% and 66%. However, both gold and platinum levels were exactly the same due to the software’s capability to absorb the requirements of the levels, were only the common requirements were able to be applied in the software. Eventually, the process of pushing the villa into nearly Zero Energy Villa using both active and passive strategies showed another huge jump in reducing energy consumption were the total yearly energy consumption was very close to zero which is 0.32 KWh, where the villa is actually considered as nearly Zero Energy Building.